Implementing Islamic Religious Education and Its Impact on Students' Morality at MAS Al-Washliyah 22, Tembung - Abdillah Dhuha (Sufiya Journal of Islamic Studies, 2023)
This study aims to explore how Islamic Religious Education (PAI) Learning as the main subject in madrasas, which is not fully owned by public schools, can be applied in real life in the formation of students' morals. The method used is qualitative with data collection techniques through in-depth interviews with key informants, namely PAI teachers, principals, and students, and analyzed through the data triangulation stage. The results of the study show that PAI learning is not only theoretical, but also applied in the form of worship and socio-religious practices. The habit of reading and memorizing the Qur'an is the main means. Thus, the implementation of PAI learning in madrassas is able to have a real influence on the formation of students' morals holistically, making madrasas a space for character education based on strong Islamic values.